Investigation of Microstructural and Mechanical Properties of AA6061 Reinforced MgO Particle. - Azmi, Muhammad Shazerin Farhan; Othman, Raudhah (Research Progress in Mechanical and Manufacturing Engineering, 2024)
The present work deals with the fabrication of AA6061 metal matrix composites reinforced with different weight percentages of MgO (0%, 1%, 2%, and 5%) produced using the powder metallurgy route. A low pressure of 318 MPa was applied for compacting the composites, which were then sintered at a temperature of 560°C for one hour. Optical microscopy was performed to study the microstructural behavior, while EDAX analysis was conducted to ensure the presence of MgO particles. The Vickers micro hardness test was conducted, revealing that the maximum hardness value of 30.86 VHN was obtained with the addition of 5% MgO particles. Additionally, compression tests were conducted to evaluate the compressive strength and overall mechanical performance of these compositions by increasing MgO content (2% and 5%) causes unanticipated changes in mechanical properties, such as decreased strength at 2% MgO and partial increase at 5% MgO.